Evaluation of Toothpaste Preparations Containing Propolis Ethanol Extract - Isna Wardaniati; Danty Indriastuty (JURNAL PROTEKSI KESEHATAN, 2022)
ABSTRACT The Trigona bee is a native Asian bee that does not have a stinger and produces propolis. Propolis is useful as an antioxidant, antimicrobial, anti-inflammatory, and antiviral. This study aims to evaluate the preparation of toothpaste which is added from propolis ethanol extract. Extraction was carried out by maceration method using 96% ethanol. Toothpaste obtained was made in four formulas based on differences in concentration, evaluation of preparation, organoleptic, homogeneity, pH test, viscosity test, foam height test and preference were carried out. Data were analyzed descriptively. The preparation of propolis ethanol extract toothpaste with various concentrations of propolis extract showed organoleptic test results in the form of a light brown color, soft texture, distinctive smell of propolis, fresh taste typical of propolis, and homogeneous, preference test of four formulas, 50% chose ordinary from 5 options. Based on each evaluation test of the paste from the preparation of propolis ethanol extract that has been made, all of them meet the criteria and requirements for physical evaluation according to SNI toothpaste No. 12-352-1995.